First Records of Paloa villadolidi from Japan with a Redescription of Odonteleotris macrodon (Teleostei: Butidae) - Saeki, Toshifumi; Nishigaki, Koji; Maeda, Ken; Kobayashi, Hirozumi (Species Diversity, 2023)
Seven specimens of Paloa villadolidi Roxas and Ablan, 1940, were collected from Okinawa and Ishigaki islands in the Ryukyu Archipelago, Japan, and their morphologies are described herein. Although this species has been considered as a synonym of Odonteleotris macrodon (Bleeker, 1853) which is redescribed in this study, the former is distinguished from the latter by having a steeper jaw (upper jaw tip not reaching orbit vs. ending below orbit center in O. macrodon), a contrasting number of canine teeth on the jaws (more upper-jaw canines than lower-jaw ones vs. more lower-jaw canines), the absence of distinct fin markings (vs. many small black spots on fin rays), no spots on the caudal-fin base (vs. with a red spot), and a higher number of cephalic sensory canal pores (17 vs. 13 or 14). This study also noted a unique canine teeth arrangement in P. villadolidi, which has canine teeth only in the anterior half of the lower jaw, unlike the canine teeth arrangement of four other butid genera (Incara Rao, 1971, Odonteleotris Gill, 1863, Ophiocara Gill, 1863, and Oxyeleotris Bleeker, 1874), which have an inner row of canine teeth in the posterior half of the lower jaw. Although further study is needed to determine the taxonomic status of P. polylepis Herre, 1927, the other nominal species of the genus, the present study tentatively considered it valid based on the original description, which described it as having a deeper body than P. villadolidi. The seven Japanese specimens were identified as P. villadolidi, as they have slenderer bodies than P. polylepis, and they represent the first Japanese records of the species.